2019
DOI: 10.1111/jre.12668
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of toothbrushing procedures performed in intensive care units in reducing the risk of ventilator‐associated pneumonia: A systematic review

Abstract: The aim of this systematic review (SR) was to assess whether toothbrushing‐based oral heath measure (OHM), performed in intensive care units, can reduce the risk of ventilator‐associated pneumonia (VAP). Dental biofilm removal has been considered important to prevent VAP. PUBMED, SCOPUS, WEB OF SCIENCE and Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched up to and including December 2018 to identify randomized clinical trials (RCT) on the use of toothbrushing procedures in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
2
20
4
13
Order By: Relevance
“…The link between VAP and dental plaque/biofilm has also been intensively studied. It was shown that brushing teeth with 0.12% chlorhexidine is also effective in inhibiting oral biofilms, reducing the incidence of VAP in patients [113]. Hua et al (2016) tested chlorhexidine mouthwash on VAP-associated critically ill patients in the ICU and proved a reduction in VAP from 26% to approximately 18%.…”
Section: Ventilator-associated Pneumoniaementioning
confidence: 99%
“…The link between VAP and dental plaque/biofilm has also been intensively studied. It was shown that brushing teeth with 0.12% chlorhexidine is also effective in inhibiting oral biofilms, reducing the incidence of VAP in patients [113]. Hua et al (2016) tested chlorhexidine mouthwash on VAP-associated critically ill patients in the ICU and proved a reduction in VAP from 26% to approximately 18%.…”
Section: Ventilator-associated Pneumoniaementioning
confidence: 99%
“…Previous studies support the suggested mechanism for microbial reduction in shorter time in Medical Clinic patients and non-intubated ICU patients than in intubated ICU patients. First, the literature reports that teeth are an important reservoir for microorganisms (Camargo et al, 2019;Vidal et al, 2017). In this study, the majority of intubated ICU patients had no teeth.…”
Section: Discussionmentioning
confidence: 73%
“…After 12 hours, the number of microorganisms decreased by 12% and 58% in both groups, respectively. Chlorhexidine is widely used for reducing the number of microorganisms in the oral cavity, and several studies have reported its influence on the prevention of VAP in hospitalized patients (Camargo et al, 2019;Deschepper et al, 2018;Meidani et al, 2018;Rabello et al, 2018;Vidal et al, 2017;Zand et al, 2017). In this context, the time necessary for microbial reduction after oral hygiene with a 0.12% chlorhexidine solution is still unclear, especially in patients with an orotracheal tube.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many chemical agents have been reported to have effects on the metabolism of bacteria and the adherence of bacterial cells. Some, such as chlorhexidine [14][15][16][17], delmopinol [17,18], and triclosan [19], have shown potent inhibitory activities against the development and maturation of biofilm. It is generally believed that the mechanism of chlorhexidine bactericidal activity is the destruction of the serosa permeability barrier against bacterial cells.…”
Section: Chemical Agentsmentioning
confidence: 99%